Development of talent management model among Indonesian civil advocates - Hendriarti, Susie Fitri (2025)
Due to the rapid growth of the advocate service sector, the increasing number of advocates, and the ease of entry into the profession, the quality of advocates has become a critical issue that deserves serious attention. One of the main drivers of change in improving advocate quality is talent management. However, despite its potential, the effectiveness of talent management remains uncertain, particularly as a relatively small percentage of talent management programs are successfully implemented. Existing literature suggests that several factors influence the effectiveness of talent management, yet its practical application still faces challenges. This study aims to identify the variables that influence talent management among advocates in Indonesia, focusing on competence, performance, success, and hard and soft skills. A quantitative approach using a purposive sampling method was employed, distributing questionnaires to 100 advocates across five major cities: Medan, Yogyakarta, Jakarta, Makassar, and Surabaya. Additionally, Focus Group Discussions (FGDs) were conducted to enrich the findings. Data analysis using SmartPLS revealed that only the competency variable had a positive and significant effect on talent management, while soft skills, hard skills, performance, and success did not show any significant impact. These results underscore the pivotal role of competence in developing and managing advocate talent effectively. The FGDs further highlighted that talent management is essential for identifying high-potential advocates and ensuring career progression that adds value to both clients and legal service institutions. This study proposes a talent management paradigm developed specifically for the advocacy profession, incorporating variables such as competence, performance, success, hard skills, and soft skills. The findings contribute to the body of knowledge in Strategic Human Resource Management (SHRM) and provide practical insights for improving the quality and professionalism of civil advocates in Indonesia, ultimately supporting better public legal services.